Nonlinear electrodynamics without birefringence - Jorge G. Russo; Paul K. Townsend (Journal of High Energy Physics, 2023)
Abstract All solutions of the no-birefringence conditions for nonlinear electrodynamics are found. In addition to the known Born-Infeld and Plebanski cases, we find a “reverse Born-Infeld” case, which has a limit to Plebanski, and an “extreme-Born-Infeld” case, which arises as a Lagrangian constraint. Only Born-Infeld has a weak-field limit, and only Born-Infeld and extreme-Born-Infeld avoid superluminal propagation in constant electromagnetic backgrounds, but all cases have a conformal strong-field limit that coincides with the strong-field limit of Born-Infeld found by Bialynicki-Birula.